State-Of-Charge Estimation of Li-Ion Battery Using Extended Kalman Filter - Feng Jin; He Yong-ling (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The Li-ion battery is studied base on its equivalent circuit PNGV model. The model parameters are identified by HPPC test. The discrete state space equation is established according to the model. The basic theory of extended Kalman filter algorithm is studied and then the filtering algorithm is set up under the noisy environments. Finally, a kind of electric car is used for testing under the UDDS driving condition. The difference between the simulation value using extended Kalman filter under the noisy environment and the theoretical value is compared. The result indicated that the extended Kalman filter keeps an excellent precision in state of charge estimation of Li-ion battery and performs well when disturbance happens. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3894